The Development of Japanese Encephalitis in Indonesia - Indrawati Sendow; Sjamsul Bahri (Indonesian Center for Animal Research and Development, 2005)
Japanese encephalitis (JE) is a zoonotic viral disease which causes encephalitis in children (5-9 years old) . The disease is transmitted by mosquitoes. The presence of JE virus, vector and reservoir host in Indonesia, will increase the concern of the possibility of JE outbreak in Indonesia. JE infection in human was reported by clinical and serological findings. Recently, JE case in Bali was declared as hyperendemic (usually sporadic) . In animals, JE infection has been confirmed by serology and viral isolation, while JE vector had been found in different species of mosquitoes by successful viral isolation from those mosquitoes. The prevention and control of JE are conducted by socialization about JE to the society, by cutting the JE transmission cycle (virus, vector and host), including pig farm relocation . The development of regional laboratories (facilities and human resources) to diagnose JE and the establishment BSL of 3 laboratory in the central laboratory institute to isolate the JE virus and to conduct further JE research on the role of animal in transmitting JE to human, must be conducted . Key words : Japanese encephalitis, epidemiology, diagnose, animals, human